2021
DOI: 10.3390/jcm10184272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Osteotomy Inclination Angle in the Sagittal Plane on the Posterior Tibial Slope of the Tibiofemoral Joint in Medial Open-Wedge High Tibial Osteotomy: Three-Dimensional Computed Tomography Analysis

Abstract: The posterior tibial slope of the tibiofemoral joint changes after medial open wedge high tibial osteotomy (MOWHTO), but little is known about the effect of the sagittal osteotomy inclination angle on the change in the posterior tibial slope of the tibiofemoral joint. The purpose of this study was to investigate the effect of the osteotomy inclination angle in the sagittal plane on changes in the posterior tibial slope after MOWHTO by comparing how anterior and posterior inclination affect the posterior tibial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…However, the present study demonstrated that even if the osteotomy opening gap ratio is adjusted to an appropriate value of 2/3 during MOWHTO 21 , the postoperative posterior tibial slope can change depending on the osteotomy inclination angle in the sagittal plane. These results are consistent with those of previous clinical studies 22,23 . In addition, some previous studies have also argued that the posterior tibial slope did not change when an osteotomy line was created parallel to the joint line 32,33 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, the present study demonstrated that even if the osteotomy opening gap ratio is adjusted to an appropriate value of 2/3 during MOWHTO 21 , the postoperative posterior tibial slope can change depending on the osteotomy inclination angle in the sagittal plane. These results are consistent with those of previous clinical studies 22,23 . In addition, some previous studies have also argued that the posterior tibial slope did not change when an osteotomy line was created parallel to the joint line 32,33 .…”
Section: Discussionsupporting
confidence: 93%
“…The changes in the posterior tibial slope were observed after MOWHTO when there was an osteotomy inclination angle with an absolute value of 10° or more between the osteotomy line and the medial tibial plateau line in the sagittal plane. Multiple factors need to be appraised during MOWHTO to prevent unwanted changes in the posterior tibial slope [20][21][22][23] . The most common factor to influence the change in the posterior tibial slope is the opening gap ratio, which is derived based on the difference between anterior and posterior osteotomy opening gaps 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations